2017
DOI: 10.1016/j.celrep.2017.11.106
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations Activating the mTOR Pathway in Dorsal Telencephalic Progenitors Cause a Continuum of Cortical Dysplasias

Abstract: Summary Focal cortical dysplasia (FCD) and hemimegalencephaly (HME) are epileptogenic neurodevelopmental malformations caused by mutations in mTOR pathway genes. Deep sequencing of these genes in FCD/HME brain tissue identified an etiology in 27/66 cases (41%). Radiographically indistinguishable lesions are caused by somatic activating mutations in AKT3, MTOR, and PIK3CA, and germline loss-of-function mutations in DEPDC5, NPRL2, and TSC1/2, including TSC2 mutations in isolated HME demonstrating a “two-hit” mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
307
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 270 publications
(328 citation statements)
references
References 53 publications
12
307
3
6
Order By: Relevance
“…1 Despite the growing body of studies addressing FCD, with more than 740 papers listed in PubMed since the release of the first international consensus classification in 2011, consistent information about their origin or timing of the lesion during brain development is still lacking. 34,36,38,[40][41][42][43] The genetic variants represent somatic mosaicisms, affecting predominantly MTOR or DEPDC5, with allele fractions of 1%-12.6 %. 34,36,38,[40][41][42][43] The genetic variants represent somatic mosaicisms, affecting predominantly MTOR or DEPDC5, with allele fractions of 1%-12.6 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite the growing body of studies addressing FCD, with more than 740 papers listed in PubMed since the release of the first international consensus classification in 2011, consistent information about their origin or timing of the lesion during brain development is still lacking. 34,36,38,[40][41][42][43] The genetic variants represent somatic mosaicisms, affecting predominantly MTOR or DEPDC5, with allele fractions of 1%-12.6 %. 34,36,38,[40][41][42][43] The genetic variants represent somatic mosaicisms, affecting predominantly MTOR or DEPDC5, with allele fractions of 1%-12.6 %.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Somatic mutations in genes belonging to the mTOR pathway have been shown to occur in the range of 15.6% to 46% of patients with FCD according to different studies. The large gap of noninformative genetic data in approximately 60%-80% of patients with FCD II, in particular those with FCD IIb, calls for extended molecular-genetic investigations integrating single-cell genome-wide DNA 38 and RNA sequencing 44 or alternative sequencing strategies 45,46 to potentially identify the pathogenic cause of FCD II. We identified variants in mTOR pathway genes in 2 of 15 patients with FCD (14.2%) including a novel likely pathogenic germline splicing variant in DEPDC5 and a single nucleotide variant of uncertain significance in AKT1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported on the prevalence of somatic variants of mTOR pathway genes in patients diagnosed with HME, showing that AKT3 and PIK3CA might be mutated in 8%–10% of the studied cases . D’Gama et al, using deep sequencing of these mTOR genes, identified an etiology in 27/66 cases (41%) . Rivière et al highlight the central role of PI3K/AKT de novo mutations in HME patients, and the power of massive parallel sequencing in the challenging context of phenotypic and genetic heterogeneity combined with postzygotic mosaicism mutations .…”
Section: Discussionmentioning
confidence: 99%
“…These approaches hold great promise for accelerating genetic stratification of patients for predicting outcomes and response to therapy. 10,11 Variants in ion channels 12 and γ-aminobutyric acid receptors 13 are also pleiotropic and arise in complex profiles in the epilepsy and general populations. 7,8 However, because of these efforts, the genetic complexity of the epilepsies has also become clear.…”
Section: From Gene To Genomementioning
confidence: 99%
“…6 The sequencing of novel variants is a highly advanced field. 11 Furthermore, the phenotypic variability of mutations indicates the presence of gene interactions and modifier pathways that can potentially be targeted for therapeutic gain. Clinical phenotypes associated with single mutations vary widely to expose a spectrum of outcomes.…”
Section: From Gene To Genomementioning
confidence: 99%